2019
DOI: 10.1002/joa3.12231
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of oral anticoagulants in atrial fibrillation patients over 80 years of age with nonsevere frailty

Abstract: Background The safety and efficacy of an oral anticoagulant (OAC) treatment and the difference between direct OACs (DOACs) and warfarin in nonsevere frail elderly patients with AF are unclear. Methods This was a retrospective and observational study of 354 patients over 80 years of age with nonsevere frailty who were diagnosed with AF and treated with OACs. Nonsevere frailty was defined as a clinical frailty scale score of <7. Bleeding and thromboembolic events during the OAC treatment were followed up. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
(27 reference statements)
0
11
0
1
Order By: Relevance
“…Mortality rates in NOAC users were similar ( Nishida et al., 2019 ; Mitchell et al., 2019 ) to even significantly lower ( Deitelzweig et al., 2019 ; Kim et al., 2019 ; Poli et al., 2019 ; Russo et al., 2019 ; Alcusky et al., 2020 ; Chao et al., 2020 ) as compared to warfarin. In terms of safety, NOACs were associated with a similar ( Giustozzi et al., 2019 ; Mitchell et al., 2019 ; Nishida et al., 2019 ; Poli et al., 2019 ; Russo et al., 2019 ; Chao et al., 2020 ) to lower ( Kim et al., 2019 ; Shinohara et al., 2019 ; Nishida et al., 2019 ; Chao et al., 2020 ; Wong et al., 2020 ) major bleeding, a similar ( Hohmann et al., 2019 ; Kim et al., 2019 ) to significantly higher ( Mitchell et al., 2019 ; Wong et al., 2020 ) gastrointestinal bleeding and a lower ( Hohmann et al., 2019 ; Kim et al., 2019 ; Mitchell et al., 2019 ; Chao et al., 2020 ; Wong et al., 2020 ) intracranial bleeding risk (except for a similar risk in one study) ( Russo et al., 2019 ) as compared to VKAs in AF patients ≥75, ≥80, ≥85 and ≥90 years old ( Shinohara et al., 2019 ; Hohmann et al., 2019 ; Nishida et al., 2019 ; Mitchell et al., 2019 ; Giustozzi et al., 2019 ; Russo et al., 2019 ; Kim et al., 2019 ; Poli et al., 2019 ; Chao et al., 2020 ). Interestingly, in AF patients ≥90 years old, the use of NOACs as compared to no anticoagulation was associated with a significantly lower risk for the composite effectiveness endpoint (stroke/SE, pulmonary embolism and death), and a borderline similar risk for major bleeding and intracranial bleeding ( Raposeiras-Roubín et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mortality rates in NOAC users were similar ( Nishida et al., 2019 ; Mitchell et al., 2019 ) to even significantly lower ( Deitelzweig et al., 2019 ; Kim et al., 2019 ; Poli et al., 2019 ; Russo et al., 2019 ; Alcusky et al., 2020 ; Chao et al., 2020 ) as compared to warfarin. In terms of safety, NOACs were associated with a similar ( Giustozzi et al., 2019 ; Mitchell et al., 2019 ; Nishida et al., 2019 ; Poli et al., 2019 ; Russo et al., 2019 ; Chao et al., 2020 ) to lower ( Kim et al., 2019 ; Shinohara et al., 2019 ; Nishida et al., 2019 ; Chao et al., 2020 ; Wong et al., 2020 ) major bleeding, a similar ( Hohmann et al., 2019 ; Kim et al., 2019 ) to significantly higher ( Mitchell et al., 2019 ; Wong et al., 2020 ) gastrointestinal bleeding and a lower ( Hohmann et al., 2019 ; Kim et al., 2019 ; Mitchell et al., 2019 ; Chao et al., 2020 ; Wong et al., 2020 ) intracranial bleeding risk (except for a similar risk in one study) ( Russo et al., 2019 ) as compared to VKAs in AF patients ≥75, ≥80, ≥85 and ≥90 years old ( Shinohara et al., 2019 ; Hohmann et al., 2019 ; Nishida et al., 2019 ; Mitchell et al., 2019 ; Giustozzi et al., 2019 ; Russo et al., 2019 ; Kim et al., 2019 ; Poli et al., 2019 ; Chao et al., 2020 ). Interestingly, in AF patients ≥90 years old, the use of NOACs as compared to no anticoagulation was associated with a significantly lower risk for the composite effectiveness endpoint (stroke/SE, pulmonary embolism and death), and a borderline similar risk for major bleeding and intracranial bleeding ( Raposeiras-Roubín et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…In terms of effectiveness, NOACs had an equal stroke/SE risk as compared to VKAs in AF patients ≥75, ≥80, ≥85, and ≥90 years old ( Avgil-Tsadok et al., 2016 ; Lai et al., 2018 ; Giustozzi et al., 2019 ; Hohmann et al., 2019 ; Nishida et al., 2019 ; Mitchell et al., 2019 ; Russo et al., 2019 ; Shinohara et al., 2019 ; Alcusky et al., 2020 ). Some studies even described a significantly lower stroke/SE ( Deitelzweig et al., 2019 ; Kim et al., 2019 ) and ischemic stroke risk ( Mitchell et al., 2019 ; Deitelzweig et al., 2019 ; Chao et al., 2020 ), as opposed to a higher stroke/transient ischemic attack (TIA) risk in one small Italian study ( Poli et al., 2019 ) and a borderline increased ischemic stroke/TIA risk for apixaban in another study due to off-label underdosing ( Alcusky et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large Asian study from the Taiwan National Health Insurance database found annual rates of thromboembolic events in patients with NVAF aged ≥ 90 years (mean CHA 2 DS 2 -VASc score 5.7) of 4.1 and 4.6/100 PY with DOACs and warfarin, respectively [ 16 ]. Single-center studies in Japan showed a much lower incidence rate of thromboembolic events (0.9 and 1.4/100 PY for DOACs and warfarin, respectively, in patients with NVAF aged ≥ 80 years [mean CHADS 2 score 2.7; mean CHA 2 DS 2 -VASc score 5.3]) [ 33 ] and a lower incidence rate of thromboembolic events (0 and 1.4% per year with DOACs and warfarin, respectively) in patients with NVAF aged ≥ 90 years (median CHADS 2 score 3; median CHA 2 DS 2 -VASc score 5) [ 34 ]. Different sample sizes and sampling methods (large national database vs. single-center medical chart) may have contributed to the different incidence rates for thromboembolic events.…”
Section: Discussionmentioning
confidence: 99%
“…We found no differences in the incidence rates of thromboembolic or bleeding events between patients treated with DOACs and those treated with warfarin. Recent studies suggested a greater benefit of DOACs over warfarin in very elderly patients with NVAF because DOACs were associated with a lower risk of major bleeding [ 13 17 , 33 ]. However, some studies suggested that the incidence of major bleeding was similar between elderly patients treated with DOACs and those treated with warfarin and that warfarin is still preferred over DOACs in patients aged ≥ 90 years who have a high thromboembolic and bleeding risk [ 32 , 34 , 38 ].…”
Section: Discussionmentioning
confidence: 99%